Funerary heritage of La Plata and citizenship: Reflections on the Universidad Nacional de La Plata and its role in the construction of local memory - Bertani, Guillermo Oscar; Sempé, María Carlota (Facultad de Filosofía y Humanidades. Museo de Antropología, 2024)
Throughout the team’s investigations, efforts were made to build knowledge about the Cementerio Municipal de La Plata, which we understand to be in danger. It is characterized by forming a funerary landscape subject to a hermeneutic interpretation that accounts for its production, its material and symbolic organization, the circulation and differential reception of meanings by the various social moments and sectors that make up and have made up the city and its surroundings. However, this knowledge constructed from the research did not manage to engage the public outside the academic sphere. Recognizing that knowledge should be a shared construction with the community to which the Universidad Nacional de La Plata is dedicated and serves, we have proposed to promote a dynamic, inclusive, and organized exchange with the residents of the locality where the cemetery is located. To this end, we aim to rescue the historical and current funerary heritage value of the cemetery, based on the commitment to build an active and engaged citizenship that appropriates, narrates, and experiences its own local history. Ultimately, the goal is to find a formula that allows us to integrate some of the theoretical aspects of our our analytical framework and resources as researchers with the interests of the community.